THE INFECTIONS of HBV, HCV and HDV in RENAL TRANSPLANT RECIPIENTS - Ercan OK; Mahmut TÖBÜ; Evren ÖZDEMİR; Fehmi AKÇİÇEK; Yaman TOKAT; Serhat BOR; Gürhun ATABAY; Yücel BATUR (Turkish Journal of Gastroenterology, 2020)
-